Model Posdaya Dalam Penuntasan Wajib Belajar Pendidikan Dasar 9 Tahun - Oos M Anwas (Jurnal Pendidikan dan Kebudayaan, 2010)
This paper aims to analyze solutions for the problems using Family and The Community Empowering (Posdaya). Theories used within this model refers to social change and community empowerment theories. Since the complexity of problems face by those hard rock society, the accomplishment of nine-year compulsory learning must be done by means of family empowerment within Posdaya. Posdaya is a forum for communications, ‘silaturahmi’, advocacy and education, and simultaneously the institution for activities to strengthen family functions in an integrated manner. Instead of establishing a new institution, the development of Posdaya can be done by optimizing the existing one by empowering activities. Posdaya become a place for discussing daily matters, especially the obstacles in accomplishing the nine-year compulsory learning, among children, parents and community that are fit with their own needs and potential/roles. Posdaya is also capable in re-developing local wisdom and social capital. At the end Posdaya is not only to solve educational problems but also to solve poverty and other social problems. For those reasons the accomplishment of nine-year compulsory learning requests cooperation across departments within coordination of welfare ministry in collaboration with local government and society. ABSTRAK Tulisan ini bertujuan mengkaji solusi dalam mengatasi masalah tersebut melalui model Pos Pemberdayaan Keluarga (Posdaya). Teori-teori yang digunakan mengacu pada teori perubahan sosial dan teori pemberdayaan masyarakat. Dengan kompleksnya masalah yang dihadapi kelompok masyarakat hard rock tersebut, penuntasan wajar 9 tahun perlu dilakukan melalui upaya pemberdayaan keluarga dalam wahana Posdaya. Posdaya merupakan forum silaturahmi, komunikasi, advokasi dan wadah kegiatan penguatan delapan fungsi-fungsi keluarga secara terpadu. Pengembangan Posdaya tidak harus membuat lembaga baru dalam masyarakat, tetapi dapat mengoptimalkan yang ada melalui aktivitas pemberdayaan. Posdaya menjadi wahana diskusi dalam memecahkan permasalahan sehari-hari, khususnya kendala kendala penuntasan wajar 9 tahun secara bersama antara anak, orang tua, dan masyarakat sesuai dengan kebutuhan dan potensi/peran masing-masing. Posdaya juga mampu membangun kembali kearifan lokal dan modal sosial. Pada akhirnya Posdaya tidak hanya memecahkan masalah pendidikan, akan tetapi juga masalah kemiskinan dan masalah sosial lainnya. Oleh karena itu penuntasan wajar 9 tahun perlu kerja sama lintas departemen di bawah koordinasi Menkokesra, terutama sektor pendidikan, kesehatan, dan kewirausahaan, bersama pemerintah daerah dan masyarakat.